1988
DOI: 10.1212/wnl.38.11.1682
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐pathologic studies in dementia

Abstract: We compared neuropsychological findings in 28 longitudinally evaluated elderly subjects with their postmortem neuropathology, including senile plaque and neurofibrillary tangle counts from standardized sections. Nine of the subjects were not demented when evaluated just prior to their death. Numerous cortical senile plaques and other changes of Alzheimer's disease (AD) occurred in six of nine nondemented old-old subjects. Five of these six subjects had shown decline on yearly neuropsychological tests but their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
238
1
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(258 citation statements)
references
References 0 publications
11
238
1
3
Order By: Relevance
“…Several investigators have noted that close to half of demented individuals in the tenth decade are likely to have no obvious pathology to explain their cognitive and functional loss [30,31]. Conversely, approximately one of every three non-demented individuals at age 85 have been reported to have senile plaques and neurofibrillary tangles at autopsy, suggesting a pathological diagnosis of AD despite the lack of clear clinical dementia syndrome [31][32][33]. Initial results in a small group of centenarians also showed that about one third of non-demented participants meet pathological criteria for AD [34].…”
Section: Clinical-pathological Correleations In the Oldest-oldmentioning
confidence: 99%
“…Several investigators have noted that close to half of demented individuals in the tenth decade are likely to have no obvious pathology to explain their cognitive and functional loss [30,31]. Conversely, approximately one of every three non-demented individuals at age 85 have been reported to have senile plaques and neurofibrillary tangles at autopsy, suggesting a pathological diagnosis of AD despite the lack of clear clinical dementia syndrome [31][32][33]. Initial results in a small group of centenarians also showed that about one third of non-demented participants meet pathological criteria for AD [34].…”
Section: Clinical-pathological Correleations In the Oldest-oldmentioning
confidence: 99%
“…In some studies, a correlation has been found between elevated levels of Aβ in the brain and cognitive decline [3], but the quantity of amyloid deposits does not seem to correlate well with the degree of cognitive impairment. Several studies have reported patients without overt symptoms of dementia, yet showing many amyloid deposits in the brain at autopsy [4]. Given the pathologic changes in the AD brain, including accumulation of neurofibrillary tangles and Aβ, reduced levels of synaptophysin, and elevated levels of glial fibrillary acidic protein (GFAP), Ingelsson and colleagues compared neuropathological changes in the temporal association cortex of AD cases with varying disease duration, with those of control brains, in an attempt to define the time course of these changes [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent form of age-associated dementia, Alzheimer's disease (AD), is histologically characterized by the formation of neurofibrillary tangles (NFTs) composed of the microtubule-associated protein tau, accompanied by extracellular formation of amyloid plaques composed of the amyloid ␤ peptide (A␤); however, it is the tau pathology in AD that most closely correlates with neuronal loss (Gomez-Isla et al, 1997) and clinical dementia (Grundke-Iqbal et al, 1986;Ihara et al, 1986;Crystal et al, 1988). The discovery that mutations in the gene for tau (MAPT ) cause FTDP-17 (frontotemporal dementia with parkinsonism-linked to chromosome 17) (Hutton et al, 1998;Spillantini et al, 1998), which is associated with tau aggregates within neurons and glia, provided conclusive evidence that abnormalities in tau were sufficient to produce neurodegeneration independent of A␤.…”
Section: Introductionmentioning
confidence: 99%